Ajuste diádico entre personas que conforman una relación de pareja y son residentes del municipio de Jamundí, Valle del Cauca (2024)
The present work was oriented with the purpose of describing the dyadic adjustment between people who form a couple relationship and are residents of the municipality of Jamundí, Valle del Cauca. Through an exhaustive search in relation to the topic in question, where the different degrees of satisfaction of dyadic adjustment that they have in the couple relationship in cohabitation are known. Therefore, the study was oriented to ten couples in a loving relationship, who voluntarily accepted to be evaluated by means of the dyadic adjustment scale (EAD). T